Question
upstudy study bank question image url

8. \( x, y \in \mathbb{Z} \) \( \frac{1}{x+5}+\frac{1}{y-4}=1 \Rightarrow x+y= \) ?

Ask by Hodgson Peterson. in Turkey
Nov 21,2024

Upstudy AI Solution

Tutor-Verified Answer

Answer

\boxed{-33}

Solution

Verilen denklemi çözmek için önce ortak payda ile yazalım: \[ \frac{1}{x+5} + \frac{1}{y-4} = 1 \] Ortak payda \( (x+5)(y-4) \) olduğuna göre, denklemi şu şekilde yazabiliriz: \[ \frac{(y-4) + (x+5)}{(x+5)(y-4)} = 1 \] Bu durumda, payı paydaya eşitleyerek: \[ y - 4 + x + 5 = (x + 5)(y - 4) \] Düzenleyelim: \[ x + y + 1 = (x + 5)(y - 4) \] Şimdi sağ tarafı açalım: \[ x + y + 1 = xy - 4x + 5y - 20 \] Her iki tarafı düzenleyelim: \[ 0 = xy - 4x + 5y - x - y - 21 \] Bu denklemi yeniden düzenleyelim: \[ xy - 5x + 4y - 21 = 0 \] Bu, \( x \) ve \( y \) için bir denklem. Şimdi \( y \) cinsinden \( x \) değerini bulalım: \[ y = \frac{5x + 21}{x - 4} \] Burada \( y \) tam sayı olabilmesi için \( x - 4 \) ifadesinin \( 5x + 21 \) ile tam bölünebilmesi gerekir. Bu durumda \( x - 4 \) değerini bulmak için \( x \) değerlerini deneyebiliriz. Örneğin, \( x = -1 \) alalım: \[ y = \frac{5(-1) + 21}{-1 - 4} = \frac{-5 + 21}{-5} = \frac{16}{-5} \quad \text{(tam sayı değil)} \] Şimdi \( x = 0 \): \[ y = \frac{5(0) + 21}{0 - 4} = \frac{21}{-4} \quad \text{(tam sayı değil)} \] Şimdi \( x = 1 \): \[ y = \frac{5(1) + 21}{1 - 4} = \frac{5 + 21}{-3} = \frac{26}{-3} \quad \text{(tam sayı değil)} \] Şimdi \( x = 2 \): \[ y = \frac{5(2) + 21}{2 - 4} = \frac{10 + 21}{-2} = \frac{31}{-2} \quad \text{(tam sayı değil)} \] Şimdi \( x = 3 \): \[ y = \frac{5(3) + 21}{3 - 4} = \frac{15 + 21}{-1} = \frac{36}{-1} = -36 \quad \text{(tam sayı)} \] Bu durumda \( x = 3 \) ve \( y = -36 \) bulduk. Şimdi \( x + y \) değerini hesaplayalım: \[ x + y = 3 - 36 = -33 \] Sonuç olarak: \[ \boxed{-33} \]

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Beyond the Answer

To solve the equation \( \frac{1}{x+5}+\frac{1}{y-4}=1 \), let's first combine the fractions: \[ \frac{(y-4) + (x+5)}{(x+5)(y-4)} = 1 \] This leads us to: \[ (y - 4) + (x + 5) = (x + 5)(y - 4) \] Simplifying the left side: \[ x + y + 1 = (x + 5)(y - 4) \] Now, expanding the right side: \[ x + y + 1 = xy - 4x + 5y - 20 \] Rearranging the equation gives us: \[ xy - 5y + 4x - x - y - 19 = 0 \] This can be simplified to: \[ xy - 5y + 3x - 19 = 0 \] Rearranging for easier expression might help here, but we can directly use a clever approach with integers. As the equation simplifies, we can make a substitution to find values for \( x \) and \( y \). Let’s try \( x + 5 = a \) and \( y - 4 = b \), then \( \frac{1}{a} + \frac{1}{b} = 1 \) gives \( a + b = ab \). The integer solutions show that \( a \) and \( b \) can be 2 and 2 or various combinations that will indicate integer solutions. From this solution path, if we directly go back to \( x \) and \( y \): 1. If \( a = 2 \) implies \( x + 5 = 2 \), which gives \( x = -3 \). 2. Similarly, \( b = 2 \) means \( y - 4 = 2\), leading to \( y = 6\). Thus, \( x + y = -3 + 6 = 3 \). Therefore, the final result is: \[ \boxed{3} \]

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy